Between Explaining Nature and Veering Away from Nature Interpretations of Synthetic Biology and Their Meaning for the Science and Religion Dialogue - Loos, Elisabeth (2019)
Synthetic biology, a project that aims to engineer »man-made living biomachines from standardized components« (Ausländer et al. 2017, 6397), has received increasing media attention in recent years thanks to its spectacular research findings. Some have claimed it represents the last step on the road towards a causal-mechanistic explanation of life. 'What I cannot build, I cannot understand,' is the fitting motto that researchers at the J. Craig Venter Institute (JCVI) encoded into the synthetic DNA of the partially synthetic bacteria Mycoplasma mycoides JCVI- syn1.0. This interpretation of the field's research suggests that natural phenomena might be wholly reduced to parameters that can be grasped by natural science. This interpretation, however, has been criticized as unreflective naturalism, particularly in the context of the dialogue between 'science and religion.' Such reductionist leanings have been justifiably debunked as metaphysical speculations that go beyond the limits of the natural-scientific methods that inform them. In this paper, I argue that the reflex (often felt in the humanities) to engage in discussions on new developments in fields like biotechnology by criticizing their alleged reductionism often fails to perceive the pragmatic character of research in the natural sciences. I draw on the theory of science to analyze some practical aspects of synthetic biology and then detail their consequences for the dialogue between 'science and religion.'
Keywords: Biotechnology; Engineering; Heuristics; Nature; philosophy of science; Science and religion; Synthetic Biology; Tinkering